If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=6x+15
We simplify the equation to the form, which is simple to understand
3=6x+15
We move all terms containing x to the left and all other terms to the right.
-6x=+15-3
We simplify left and right side of the equation.
-6x=+12
We divide both sides of the equation by -06 to get x.
x=-2
| -1.3x-2.5+2.4x=-6.9 | | X=-x-7+3 | | X=-2x+4-7 | | 7x+33=4x | | -x-8=7x-8 | | 5/1/2+p=6 | | x/19.7=0.6091370558338 | | 3x-10=-2x-7+2 | | y/3.7-1.5=-2.8 | | 3/5(p-30)=-4 | | X=6x+8-1 | | 5squared=8x-6 | | 35=5(7+2x) | | 5-2a/-3=5/11 | | 9y-3=180 | | 8y-4=90 | | (2x^4y^8)^3/(4x^8y^4)^2 | | -1/5y=x+4 | | 5.5-2.9m=-2.1+3m | | 12(x+3)=2(x+3)-3x | | 7h-14+17=3 | | 3(2x-3)-2x=-x+1 | | 3x+1*2x+1=22 | | 11s=15 | | 1.8/6.5=x/11 | | 81=15x(x-7) | | 5/6.5=x/11 | | 8x+72-11= | | 8-0.6x=23 | | 0.2x-3=9 | | 72d+45+13=12d-2 | | 6b^2-39b+63=0 |